ENERGY EFFICIENCY OF LOW POWER WIND - Sineglazov , V. M.; Zelenkov , O. A.; Sochenko , P. S. (Problems of Informatization and Management, 2021)
The article substantiates the feasibility of using low-power wind turbines located on the roofs of high-rise buildings in large cities.